The absence of oestrogen receptor beta disturbs collagen I type deposition during Achilles tendon healing by regulating the IRF5‐CCL3 axis. Issue 17 (10th August 2020) - Bian, Xuting; Liu, Tianyao; Yang, Mingyu; Gu, Chengyi; He, Gang; Zhou, Mei; Tang, Hong; Lu, Kang; Lai, Fan; Wang, Feng; Yang, Qiandong; Gustafsson, Jan‐Åke; et al.
Abstract: Achilles tendon healing (ATH) remains an unanswered question in the field of sports medicine because it does not produce tissue with homology to the previously uninjured tissue. Oestrogen receptor β (ERβ) is involved in the injury and repair processes of tendons. Our previous study confirmed that ERβ plays a role in the early stage of ATH by affecting adipogenesis, but its role in extracellular matrix (ECM) remodelling is unknown. We established a 4‐week Achilles tendon repair model to investigate the mechanism through which ERβ affects ATH at the very beginning of ECM remodelling phase. In vitro studies were performed using tendon‐derived stem cells (TDSCs) due to their promising role in tendon healing. Behavioural and biomechanical tests revealed that ERβ‐deficient mice exhibit weaker mobility and inferior biomechanical properties, and immunofluorescence staining and qRT‐PCR showed that these mice exhibited an erroneous ECM composition, as mainly characterized by decreased collagen type I (Col I) deposition. The changes in gene expression profiles between ERβ‐knockout and WT mice at 1 week were analysed by RNA sequencing to identify factors affecting Col I deposition. The results highlighted the IRF5‐CCL3 axis, and this finding was verified with CCL3‐treated TDSCs. These findings revealed that ERβ regulates Col I deposition during ATH via the IRF5‐CCL3 axis.